Assessment of post-harvest losses along the tomato value chain in Benin - Fassinou Hotegni, Ir. V. Nicodeme; Salaou, Mouizz; Dossa, Glory Côme; Elegbede, Dorella; Atikpa, Harris (CGIAR System Organization, 2024)
This study is conducted as part of Work Package 4 (WP4) within the One CGIAR Fruit and Vegetables for Sustainable Healthy Diets (FRESH) project. The overarching aim of this project is to enhance fruit and vegetable production through a comprehensive, end-to-end approach across four target countries, including Benin. WP4 specifically addresses challenges related to post-harvest management and fostering inclusive market systems.